2015
DOI: 10.1104/pp.15.01529
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Quantification of Peroxisome Tethering to Chloroplasts in Tobacco Epidermal Cells Using Optical Tweezers

Abstract: Peroxisomes are highly motile organelles that display a range of motions within a short time frame. In static snapshots, they can be juxtaposed to chloroplasts, which has led to the hypothesis that they are physically interacting. Here, using optical tweezers, we tested the dynamic physical interaction in vivo. Using near-infrared optical tweezers combined with TIRF microscopy, we were able to trap peroxisomes and approximate the forces involved in chloroplast association in vivo in tobacco (Nicotiana tabacum)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 48 publications
(67 reference statements)
0
82
0
Order By: Relevance
“…These findings indicate that PEX11a is an important component of rapid ROS-mediated stress perception, with peroxules possibly being involved in regulating ROS accumulation to protect cells against oxidative stress. Peroxules have been reported to be associated with chloroplasts (Sinclair et al, 2009;Oikawa et al, 2015;Gao et al, 2016) and mitochondria , suggesting that they may contribute to the regulation of the excess H 2 O 2 produced in these organelles and may also favor interorganelle communication and transport. Peroxisomes contain enzymatic and nonenzymatic defense mechanisms to deal with different types of ROS such as O 2 .2 and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that PEX11a is an important component of rapid ROS-mediated stress perception, with peroxules possibly being involved in regulating ROS accumulation to protect cells against oxidative stress. Peroxules have been reported to be associated with chloroplasts (Sinclair et al, 2009;Oikawa et al, 2015;Gao et al, 2016) and mitochondria , suggesting that they may contribute to the regulation of the excess H 2 O 2 produced in these organelles and may also favor interorganelle communication and transport. Peroxisomes contain enzymatic and nonenzymatic defense mechanisms to deal with different types of ROS such as O 2 .2 and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…After using optical tweezers to investigate peroxule functionality, Gao et al (2016) have suggested that peroxules play a role in establishing and maintaining connections and communication between organelles in the intracellular environment, particularly with those that have different motilities or are spatially separated. However, we believe that the functionality of these extensions could be also specifically related to the ROS metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This is quite different to optical tweezers which uses submicron precision to specifically "pull" rather than "push" an organelle. Both approaches have been used to establish physical connections between peroxisomes and chloroplasts (Oikawa et al, 2015;Gao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Gao et al (2016) developed a quantifiable platform for using optical tweezers to measure organelle interactions in intact cells, more specifically the interaction between peroxisomes and chloroplasts. Here, using an automated platform to trap a peroxisome, users moved it a set distance at a set speed, and then monitored and quantified the effects on the organelle during this process; was it trapped?…”
Section: Discussionmentioning
confidence: 99%
“…Peroxules can mediate interorganellar contacts, such as among peroxisomes and ER (Sinclair et al, 2009), oil bodies (Thazar-Poulot et al, 2015), mitochondria (Jaipargas et al, 2016), and chloroplasts (Gao et al, 2016). Moreover, peroxules can respond to environmental signals.…”
Section: Future Perspectivesmentioning
confidence: 99%